Functional outcome is tied to dynamic brain states after mild to moderate traumatic brain injury. Issue 3 (21st October 2019) - van der Horn, Harm J.; Vergara, Victor M.; Espinoza, Flor A.; Calhoun, Vince D.; Mayer, Andrew R.; van der Naalt, Joukje
Abstract: The current study set out to investigate the dynamic functional connectome in relation to long‐term recovery after mild to moderate traumatic brain injury (TBI). Longitudinal resting‐state functional MRI data were collected (at 1 and 3 months postinjury) from a prospectively enrolled cohort consisting of 68 patients with TBI (92% mild TBI) and 20 healthy subjects. Patients underwent a neuropsychological assessment at 3 months postinjury. Outcome was measured using the Glasgow Outcome Scale Extended (GOS‐E) at 6 months postinjury. The 57 patients who completed the GOS‐E were classified as recovered completely (GOS‐E = 8; n = 37) or incompletely (GOS‐E < 8; n = 20). Neuropsychological test scores were similar for all groups. Patients with incomplete recovery spent less time in a segregated brain state compared to recovered patients during the second visit. Also, these patients moved less frequently from one meta‐state to another as compared to healthy controls and recovered patients. Furthermore, incomplete recovery was associated with disruptions in cyclic state transition patterns, called attractors, during both visits. This study demonstrates that poor long‐term functional recovery is associated with alterations in dynamics between brain networks, which becomes more marked as a function of time. These results could be related to psychological processes rather than injury‐effects, which is an interesting area for further work. Another natural progression of the current study is to examine whether these dynamic measures can be used to monitor treatment effects.